Low incidence of gastrointestinal adverse events over time with a fixed‐ratio combination of insulin glargine and lixisenatide versus lixisenatide alone. Issue 11 (21st August 2018) - Trujillo, Jennifer M.; Roberts, Michelle; Dex, Terry; Chao, Jason; White, John; LaSalle, James
Abstract : This post hoc analysis of gastrointestinal (GI) adverse events (AEs) from the phase 3 LixiLan‐L (NCT02058160) and LixiLan‐O (NCT02058147) trials aimed to determine the frequency and timing of nausea, vomiting, and diarrhoea for iGlarLixi, a titratable, fixed‐ratio combination of insulin glargine 100 units/mL (iGlar) and lixisenatide, versus iGlar alone or iGlar and lixisenatide alone, in patients with type 2 diabetes uncontrolled with oral antidiabetes drugs (OADs) or basal insulin ± OADs. In iGlarLixi‐treated patients, the rate of GI AEs during the initial weeks of treatment was lower versus patients treated with lixisenatide alone (9.6% and 11.7% of iGlarLixi‐treated patients in LixiLan‐L and LixiLan‐O, respectively, vs. 27.5% of lixisenatide‐treated patients in LixiLan‐O). Beyond day 60, these rates were generally low and similar to those of lixisenatide. These lower rates are likely due to the gradual titration of lixisenatide in iGlarLixi. Median durations of intermittent GI AEs in the iGlarLixi arms were 6.0, 2.0 and 2.5 days (LixiLan‐L), and 5.0, 1.0 and 3.5 days (LixiLan‐O), respectively. iGlarLixi‐associated GI AEs were transient, mostly mild or moderate in severity, and occurred mainly during initial titration.